Toward a Reevaluation of Siegfried Kracauer and the Frankfurt School - Daniel Sullivan (tripleC: Communication, Capitalism & Critique)
This essay reviews the anthology Siegfried Kracauer: Selected Writings on Media, Propaganda, and Political Communication (2022), edited and with translations by Jaeho Kang, Graeme Gilloch, and John Abromeit. The editors describe the volume as "a selection of Kracauer’s diverse materials on propaganda and political communication – texts hitherto unavailable in English or strewn among different […] journals, periodicals, and magazines" (2). Beyond this, Selected Writings presents readers and scholars with an opportunity to re-evaluate the legacy of Siegfried Kracauer, particularly in connection with the strands of mutual influence and parallel thought between his work and the development of early Frankfurt School critical theory. The volume contains remarkable and largely unpublished work on totalitarian propaganda in film; the manipulative devices of the U.S. advertising industry of the 1940s and 50s; and philosophy of science in the area of sociologically informed empirical research.